2018
DOI: 10.1097/ajp.0000000000000601
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of the Effectiveness of Psychological Interventions Delivered by Physiotherapists on Pain, Disability and Psychological Outcomes in Musculoskeletal Pain Conditions

Abstract: The results indicate that psychological interventions delivered by physiotherapist show promise to improve health outcomes, particularly psychological outcomes, in musculoskeletal pain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
91
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 77 publications
4
91
3
Order By: Relevance
“…A recent systematic review and metaanalysis indicated moreover that psychological interventions delivered by physiotherapists were promising to improve psychological factors in musculoskeletal pain conditions. 63 This review results also highlight potential future research paths. factor, the influence of the psychological factor on the relation between a predictor and an outcome should be analyzed.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A recent systematic review and metaanalysis indicated moreover that psychological interventions delivered by physiotherapists were promising to improve psychological factors in musculoskeletal pain conditions. 63 This review results also highlight potential future research paths. factor, the influence of the psychological factor on the relation between a predictor and an outcome should be analyzed.…”
Section: Discussionmentioning
confidence: 90%
“…60 Multidimensional biopsychosocial treatment that addresses physical and psychological factors related to perceived pain and disability is an effective treatment approach in chronic pain patients. [61][62][63] Patient education to expand patients' understanding regarding pathology, pain and influencers of pain and disability (e.g. psychological factors such expectation of recovery, self-efficacy, fear avoidance, pain catastrophizing by means of cognitive behavioral approach) 64,65 seems essential as it is shown in recent qualitative studies that persons with shoulder pain believed that their pain was caused by structures local to the shoulder region.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, the authors suggested that different testing paradigms may be affected differently by psychological factors . Nevertheless, psychological treatments might be effective for reducing pain, even when delivered combined with physiotherapy for pain and disability by physiotherapists …”
Section: Discussionmentioning
confidence: 99%
“…For musculoskeletal disorders, the predominant contemporary model consists of an integrative and multidimensional biopsychosocial theoretical framework (Gatchel et al 2007). The increasing understanding of key psychological factors in the perpetuation of pain and pain-related disability has resulted in multiple treatment modalities for musculoskeletal disorders, and the effectiveness of psychological approaches in the management of these disorders has been evaluated in numerous meta-analyses (see e.g., Ehde et al 2014; Guerrero Silva et al 2018; Markozannes et al 2017; Williams et al 2012). Nonetheless, the effectiveness of psychological interventions is still inconsistent according to outcome research on return to work (RTW).…”
Section: Introductionmentioning
confidence: 99%